KONTRIBUSI PASRAMAN WIDYA PRAKANTY DALAM MENINGKATKAN PENDIDIKAN SISWA HINDU - I Wayan Sapta Wigunadika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The material taught in Pasraman Widya Prakanty Br. Bayad, Kedisan Village,Tegallalang District, Gianyar Regency as follows: Meaning and function of upakara means. Constraints experienced by Pasraman Widya Prakanty in improving the education of Hindu students are: lack of facilities and nfrastructure that support pasraman activities, lack of coaches or competent teachers in accordance with the program of religious development so that nowstill fostered by personnel who are not their field. Pasraman Widya Prakanty’s contribution in improving the education of Hindu students is contribution in the field of education and contribution in the religious field. Based on the above conclusions can be submitted suggestions as follows. From the description of the implementation of Pasraman Widya Prakanty, to the customary teachers, teachers and the community still programmed pasraman and managed rofessionally. Suggested to Hindu children, should be more appreciate and practice the teachings of religion as a guide in doing so not fall into the things that are misleading. Thus religious and cultural values can be maintained and sustainable. To other researchers who are interested in researching this issue to be more broadly developed, about the scope and point of view are different, especially the things that are not reached in this study. So that obtained a better result and more perfect.